The Cat in The Hat Comes Back - Dr Seuss (Random House Inc, 1958)
A picture book-sized, jacketed edition of the popular sequel to The Cat in the Hat follows the struggles of two youngsters who, when revisited by the mischievous Cat, are subjected to an army of Little Cats and an ever-spreading pink mess.
Keywords: Animals; Juvenile Fiction